DESAIN SISTEM AKUNTANSI PENJUALAN PADA UMKM MADE U DESIGN - Thomas, Michelle Esther Julia Irene; Racib, Safitri; Makahaube, William G.; Sondakh, Winda A.I. (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Printing UMKM is a business that can be started from small scale and affordable capital, it can be said that now the UMKM Printing business is in great demand by the public because it is considered popular and profitable. UMKM Made U Design is one of the businessess that provides shirt screen printing designs, Business actors in Made U Design do not yet have detailed sales accounting system. The purpose of this study wasa to design a Sales Accounting System at UMKM Made U Design. This type of research is descriptive qualitative. Data sources are conducted through interviews, observations and literature studies. The benefit for business actors is that sales activities are systemized in detail. For researchers, it can increase knowledge about the Sales Accounting System and for institusions to add partners in the development of science and technology.